2007
DOI: 10.1038/sj.hdy.6800958
|View full text |Cite
|
Sign up to set email alerts
|

Habitat size and the genetic structure of a cyclical parthenogen, Daphnia magna

Abstract: In populations of a cyclical parthenogen, the diversity of clonal lineages, derived from sexually produced eggs, declines during the parthenogenetic phase. Even though Daphnia magna populations from small ponds may harbour millions of individuals, we show that observed clonal and allelic diversity in populations from such small water bodies are lower than in populations from larger water bodies. Populations from small water bodies also show significant fluctuations in allele frequencies among years and a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 29 publications
2
42
2
1
Order By: Relevance
“…For L. parvispinus and Paralimnadia sp., it was the appearance of private (or novel) haplotypes observed in each active population, which demonstrated best the stochastic effects of bet-hedging and temporal dispersal. Similar appearances of novel haplotypes were observed for other Branchiopoda-including other Spinicaudata as well as Cladocera-and perennial plants (e.g., Cabin, 1996;Brendonck & De Meester, 2003;Vanoverbeke et al, 2007;Rother et al, 2010;Hülsmann et al, 2012;Brantner et al, 2013), illustrating that only a fraction of the resting egg bank's genetic diversity enters each active population (see also McCue & Holtsford, 1998). We assume that the genetic composition of each active population is shaped by two stochastic processes: (1) stochasticity resulting from hatching from a wellmixed, unstructured egg bank (including effects of bet-hedging and temporal dispersal) and (2) genetic drift acting on each active population from the onset of hatching.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…For L. parvispinus and Paralimnadia sp., it was the appearance of private (or novel) haplotypes observed in each active population, which demonstrated best the stochastic effects of bet-hedging and temporal dispersal. Similar appearances of novel haplotypes were observed for other Branchiopoda-including other Spinicaudata as well as Cladocera-and perennial plants (e.g., Cabin, 1996;Brendonck & De Meester, 2003;Vanoverbeke et al, 2007;Rother et al, 2010;Hülsmann et al, 2012;Brantner et al, 2013), illustrating that only a fraction of the resting egg bank's genetic diversity enters each active population (see also McCue & Holtsford, 1998). We assume that the genetic composition of each active population is shaped by two stochastic processes: (1) stochasticity resulting from hatching from a wellmixed, unstructured egg bank (including effects of bet-hedging and temporal dispersal) and (2) genetic drift acting on each active population from the onset of hatching.…”
Section: Discussionsupporting
confidence: 72%
“…The latter may be of particular importance for neutral markers, which are not affected by fluctuating selection and whose frequencies may vary independently of potential selection pressures. Indeed, studies have indicated changes in the genetic composition of successive active populations, which may be related to stochastic effects (e.g., Vanoverbeke et al, 2007;Rother et al, 2010;Hülsmann et al, 2012;Brantner et al, 2013). This may result in stochastic variation of genotype frequencies between consecutive active populations, thereby impacting assessments of among population differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Although historical effects (e.g., postglacial recolonization processes) could potentially explain that northern populations have lower diversity, such effects are less likely to operate on microsatellite diversity due to the higher mutation rates in these markers. Also in D. magna, pond area and genetic and clonal diversity were significantly correlated in 17 ponds in Belgium using four allozyme loci (Vanoverbeke et al, 2007). In Artemia sinica populations, genetic diversity, as estimated from allozymes, was correlated with habitat size (Naihong et al, 2000).…”
Section: Introductionmentioning
confidence: 80%
“…Cladocerans, particularly members of the genus Daphnia, are known to exhibit a remarkable ability to adapt morphologically, physiologically and/or behaviorally to environmental change (e.g. Grant and Bayly, 1981;Kreuger and Dodson, 1981;Hebert and Grewe, 1985;Ranta and Tjossem, 1987;Hembre and Megard, 2006;Hülsmann and Wagner, 2007;Vanoverbeke et al, 2007). This functional flexibility, in combination with their parthenogenetic reproduction and ease of laboratory culture, has resulted in their emergence as model organisms for many scientific fields, prime among them ecotoxicology and toxicogenomics (e.g.…”
Section: Introductionmentioning
confidence: 99%